The impact of a peer coaching programme on the academic performance of undergraduate students: a mixed methods study. - Jill Alexandra Andreanoff (Association for Learning Development in Higher Education (ALDinHE), 2016)
Peer support interventions have been widely used within the higher education sector as a means to enhance student success and retention. However, much of the evidence to measure the impact of mentoring and coaching has relied on anecdotal, self-reported evidence from the participants. In addition, there is much confusion in the terms todescribe peer support interventions, making it difficult to compare and contrast the different programmes. The need for evidence of a more robust, quantitative nature has long been called for by a number of authors such as Jacobi (1991), Capstick et al. (2004) and Medd (2012). This mixed methods case study of an extant peer coaching programme in higher education in the UK makes explicit the process of the coaching intervention, measuring the impact on academic attainment in the form of module grade data. In addition, the use of a control group enables a comparison to be made of the academic attainment of non-coached students with those who received peer coaching. Academic behaviour confidence of those who were coached was also measured pre- and post-coaching using the Sander and Sanders (2009) ABC questionnaire. There was found to be a significant impact in the attainment of students who received coaching when compared to those students in the control group who did not. The peer coaching had a beneficial impact in particular for those in their first year of study and those who were performing less well at the outset, as well as students within the Business School. A significant increase in the academic behaviour confidence was found in those who received coaching as well as a reduced attrition rate when compared to those in the control group.